Investigating the Comparative Suitability of Traditional and Task-Specific Think Aloud Training. Issue 1 (February 2020) - Birch, Phil D. J.; Whitehead, Amy E.
The think aloud (TA) protocol is used to capture conscious cognition for wide ranging applications. However, the methods used to train the TA technique have been inconsistent, involving a mixture of both traditional guidelines and task-specific examples. This study aimed to examine how best to train the TA process. We recruited 20 competitive golfers as research participants, and we randomly assigned them to equal sized groups of traditional TA training as described by Ericsson and Simon and task-specific training in which participants were familiarized with TA via task-specific examples. Following training, all participants performed a golf task and were asked to TA. We transcribed audiotapes of their verbatim TA content and analyzed them using a deductive framework. We also collected various social validation self-report measures to assess participant perceptions of TA training. Overall, we found no significant differences in the frequency or type of TA verbalizations when comparing traditional and task-specific TA training groups. However, participants in the task-specific training group reported more favorable perceptions of training and found training significantly clearer than did participants in the traditional training group. We suggest that these findings support traditional TA training following Ericsson and Simon's training guidelines, but adding task-specific examples seems to increase the familiarity of TA use and facilitate more reliable and accurate cognition data for research use.